2021
DOI: 10.1177/09722629211002314
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effectiveness of a Social Media-based Counseling Intervention on Interest, Entrepreneurial Skills, and Behavioural Intention Towards Painting Among Youth Without Paid Jobs in Nigeria

Abstract: In this study, we made use of the human capital theory (HCT) and the theory of planned behaviour (TPB) to develop a model that explains the effectiveness of a social media–based intervention on interest, entrepreneurial skills and behavioural intention towards painting among young graduates without paid employment in Nigeria. The study included an experiment involving 470 (235 control-group and 235 treatment-group) participants who were not on the payroll of any organization at the time of the study. The quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…It is not sufficient to possess skills; such skills must be able to put food on the table for those who possess them. Okpara et al [ 12 ] in a study reported that many people with art skills do not have jobs. Accordingly, they argued that entrepreneurship, especially in arts, is one of the ways that people with art skills can improve their income.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not sufficient to possess skills; such skills must be able to put food on the table for those who possess them. Okpara et al [ 12 ] in a study reported that many people with art skills do not have jobs. Accordingly, they argued that entrepreneurship, especially in arts, is one of the ways that people with art skills can improve their income.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Researchers [ 11 , 12 ] pay greater attention to investigating issues related to technical skill acquisition as though skill acquisition by itself will automatically result in an improvement in income and the earning capacities of those with such skills. According to a study [ 13 ] entrepreneurial competence is essential for people to survive as well as market their potential with a view to improving their economic abilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media can strongly affect audiences' use of language (Ekwueme and Ebiere, 2019), purchasing behaviors (Asogwa et al. , 2020) and personal interests (Anibueze et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social media can strongly affect audiences' use of language (Ekwueme and Ebiere, 2019), purchasing behaviors (Asogwa et al, 2020) and personal interests (Anibueze et al, 2021). The social media platform Twitter has been studied extensively as a social TV platform in recent years (e.g.…”
Section: Social Media Engagementmentioning
confidence: 99%